Investment in stadia and regional economic development: evidence from FIFA World Cup 2006 - Arne Feddersen; André L. Grötzinger; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
Using the case of the new stadiums for the FIFA World Cup 2006 in Germany, this paper is the first multivariate work that examines the potential income and employment effects of new stadiums outside of the USA. This study is also the first work on this topic that conducts tests on the basis of a (serial correlation consistent) Difference-in-Difference model with level and trends. As a robustness check, we use the ignoring time series information model in a form that is modified for nonsynchronous interventions. We were not able to identify income or employment effects of the construction of new stadiums for the FIFA World Cup 2006, which are significantly different from zero.
Keywords: H54; L83; R12; R53; 330; Regional Economics; Stadia Infrastructure; Difference-in-Difference Model